Derivative Contracts and Risk Management - Urban, Jiří; Strouhal, Jiří, 1980-; Witzany, Jiří, 1966-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
Aim of this thesis is to provide a thorough overview of financial derivatives, their role on global financial markets, use of derivatives in risk management applications. Also, this thesis addresses options pricing and introduces two most common options pricing models -- binomial tree model and Black-Scholes-Merton model. Section 1 provides overview of most common derivatives and Section 2 includes risk management theory and application examples. Sections 3 and 4 are dedicated to options pricing -- both from theoretical and practical point of view. Practical part on options pricing is dedicated to convergence of binomial tree model to Black-Scholes-Merton model.
Vedoucí práce: Jiří Strouhal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses